Reading Islam : life and politics of brotherhood in modern Turkey - Vicini, Fabio, 1981- (Social, Economic and Political Studies of the Middle East and Asia;, 2020)
In Reading Islam Fabio Vicini offers a journey within the intimate relations, reading practices, and forms of intellectual engagement that regulate Muslim life in two enclosed religious communities in Istanbul. Combining anthropological observation with textual and genealogical analysis, he illustrates how the modes of thought and social engagement promoted by these two communities are the outcome of complex intellectual entanglements with modern discourses about science, education, the self, and Muslims' place and responsibility in society. In this way, Reading Islam sheds light on the formation of new generations of faithful and socially active Muslims over the last thirty years and on their impact on the turn of Turkey from an assertive secularist Republic to an Islamic-oriented form of governance.